Effect of Aspergillus flavus on lipid peroxidation and activity of antioxidant enzymes in midgut tissue of Spodoptera litura larvae. (22nd July 2021) - Kaur, Mandeep; Chadha, Pooja; Kaur, Sanehdeep; Kaur, Amarjeet
Abstract: In the present study, effect of Aspergillus flavus was analysed on lipid peroxidation and activities of antioxidant enzymes in midgut of Spodoptera litura. Fungus was administered to the larvae of S. litura using artificial diet method having 1.34 mg/mL (LC50) concentration. The fungus toxicity was observed after 24, 48, 72 and 96 h post treatment in the midgut tissue of insect larvae by examining lipid peroxidation (MDA content) and activities of antioxidant enzymes viz superoxide dismutase (SOD), catalase (CAT), ascorbate peroxidase (APOX) and glutathione- S -transferase (GST) as oxidative stress markers. Additionally, repair of the damage caused due to fungal treatment was also assessed to decipher the longevity of effect by giving control diet to the exposed larvae for two days after particular time exposure using same parameters. In particular, significant ( p ≤ 0.05) increased level of lipid peroxidation and antioxidant enzymes activities was observed in all exposure time groups with respect to control which showed that midgut of exposed larvae has oxidative predominance. Repair studies demonstrated the negligible repair in insect larvae. In conclusion, A. flavus contributed to strong oxidative stress and toxicity in S. litura larvae.